Systematic pan-cancer analysis identifies gasdermin B as an immunological and prognostic biomarker for kidney renal clear cell carcinoma - Liu, Xuehe; Xie, Feiyan; Ding, Jin; Li, Suhua; Li, Jixi (Frontiers in Oncology, 2023)
Gasdermins (GSDMs)-mediated cell lytic death plays an essential role in immunity and tumorigenesis. Despite the association of gasdermin B (GSDMB) with the tumorigenesis of various cancers, whether GSDMB functions as a prognostic biomarker in renal cell carcinoma remains poorly understood. Here, we explored the potential immunological functions and the prognostic value of GSDMB across multiple tumors with the TCGA and GTEx databases, including analyzing the relationship between GSDMB expression and prognosis, tumor-immune system interactions, immunomodulators, and immune cell infiltration of different tumors. Importantly, elevated expression of GSDMB was an essential factor for the poor prognosis of kidney renal clear cell carcinoma (KIRC) patients, suggesting it might be helpful to predict a survival benefit from a clinical therapy regimen. Furthermore, GSDMB expression promoted the level of CD4+ T cell infiltration of the tumors, while significantly negatively associated with iDC in KIRC. Additionally, we identified TNFRSF25 and TNFSF14 as immunostimulators highly correlated with GSDMB expression. KEGG and GO enrichment analysis showed that GSDMB and its interacting proteins might affect tumor growth through the serine metabolism pathway. Our current results demonstrate a promising therapeutic strategy targeting GSDMB and provide new insights into GSDMB as an immunological and prognostic biomarker for KIRC.